Local wisdom-based tourism and creative economy development strategies in Cisantana Village - Aep Saefullah; Ahmad Fadli; Hilda Fariha (Jurnal Pariwisata Pesona, 2023)
The objective of this research is to perform an analysis aimed at identifying tourism development strategies for Cisantana village in the Cigugur district of Kuningan regency, as no tourism development model has been previously studied in this area. Semi-structured interviews with 100 respondents, including village authorities, company owners, tourist object managers, and Kuningan district office officials, were conducted throughout the research's six-month period from February to August 2023. It employs descriptive qualitative analysis. Literature, FGDs, interviews, and observation are used to acquire data. Using Nvivo 12 software, qualitative data analysis approaches were used. The findings indicated that the tourism and creative economy development model based on local wisdom in Cisantana village can be developed through strategies including a) prioritizing local tourism businesses, b) contributions from all parties, c) community empowerment, d) cooperation, collaboration, and synergy across sectors, e) strengthening partnerships so they don't become competitors, f) sustainability and continuity, g) infrastructure improvement, h) research studies and development applications. The benefits of tourist development and creative companies include great tourism potential, boosting local economies, enhancing local knowledge, and chances to build businesses and jobs for nearby areas. The marginalization of farmer groups, the decrease of cultural culture, the appearance of trash, waste, and pollution in tourist regions, as well as the loss of local knowledge, are the negative effects. The public sector, the government, and other relevant parties can benefit from this study. The research's overall goal is to improve public awareness of the value of fostering a creative economy and tourism based on local knowledge.